2005
DOI: 10.2337/diacare.28.7.1649
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Overweight on Chronic Microvascular Complications in Type 1 Diabetic Patients

Abstract: OBJECTIVE -To investigate a possible association of BMI with retinopathy and neuropathy in type 1 diabetes. Retinopathy and neuropathy may not only be related to glycemic control and diabetes duration but also to blood pressure and BMI.RESEARCH DESIGN AND METHODS -A total of 592 type 1 diabetic patients without nephropathy were studied (M/F: 324/268; age: 41 Ϯ 12 years; duration: 19 Ϯ 11 years; HbA 1c [A1C]: 7.9 Ϯ 1.1%). Patients were subdivided according to BMI: 168 men and 146 women with BMI Ͻ25 kg/m 2 , and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
4
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 53 publications
9
88
4
7
Order By: Relevance
“…However, whether obesity is an independent risk factor for development of neuropathic pain disorders is not entirely clear. For example, De Block and colleagues found that BMI was not independently associated with neuropathy in a population of patients with type 1 diabetes [62]. Others have found that the incidence of neuropathy among those with type 1 diabetes who received care at specialty clinics was related to duration of disease and glycosylated hemoglobin values (the two major known determinants of neuropathy) and that, after controlling for these, higher BMI was one among many cardiovascular risk factors associated with cumulative incidence of neuropathy [63].…”
Section: Mechanisms: Explaining the Relationship Between Pain And Ovementioning
confidence: 99%
“…However, whether obesity is an independent risk factor for development of neuropathic pain disorders is not entirely clear. For example, De Block and colleagues found that BMI was not independently associated with neuropathy in a population of patients with type 1 diabetes [62]. Others have found that the incidence of neuropathy among those with type 1 diabetes who received care at specialty clinics was related to duration of disease and glycosylated hemoglobin values (the two major known determinants of neuropathy) and that, after controlling for these, higher BMI was one among many cardiovascular risk factors associated with cumulative incidence of neuropathy [63].…”
Section: Mechanisms: Explaining the Relationship Between Pain And Ovementioning
confidence: 99%
“…However, studies that have investigated the contributions of the individual components have revealed mixed results 15, 16, 17, 18, 19, 20, 21. We have recently shown that diabetes, prediabetes, and obesity are the main metabolic components associated with peripheral neuropathy in a United States obese population 22.…”
Section: Introductionmentioning
confidence: 99%
“…A higher plasma concentration of leptin is associated with the development and progression of microvascular complications in patients with T2DM (17)(18)(19). At the molecular level the effectof leptinonendothelial functionis unclear as leptin both stimulates the activity ofeNOS andreducesthe bioavailability ofLargininerequiredfor NO synthesis (20)(21)(22). In addition, the results of studies exploring the relationship between leptin and microvascularcomplications in patients with T1DM…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…In T2DM plasma concentration is inversely associated with retinopathy (25) and urinary albumin excretion rate (UAE), an early marker of renal microvasculature (26). However, in T1DM the relationof adiponectinwithretinopathy, albuminuriaandnephropathyis not fully understood (20,(29)(30)(31). Insome studies a positive correlationof adiponectinwithretinopathy andalbuminuria in T1DM was found (29,30).…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%